Enhancing the solid fuel properties of durian peel through torrefaction under mechanical pressure - Chaioan, Waritsara; Chummek, Phoipailin; Nuliang, Kitipa; Jadsadajerm, Supachai (Frontiers in Engineering Innovation Research, 2026)
This study investigated the enhancement of the solid fuel properties of durian peel through torrefaction under mechanical pressure to improve its chemical and physical characteristics prior to its use as a solid fuel and as a feedstock for biochar production. The experiments were carried out at 280, 300, 320, and 340 °C under pressures of 30, 60, 90, and 120 bar. The results showed that increasing temperature and pressure reduced the mass yield from 89.07% to 41.83%, while the carbon content, fixed carbon content, and higher heating value increased. The carbon content increased from 48.43% to 69.87%, the fixed carbon content increased from 13.97% to 41.39%, and the higher heating value increased from 18.01 to 25.52 MJ/kg. The increase in higher heating value was related to the decreases in the H/C and O/C atomic ratios, as well as the reduction of oxygen-containing functional groups in the biomass structure. However, when the energy yield was considered, the condition of 340 °C and 120 bar, although giving the highest higher heating value, resulted in an energy yield of only 59.27% and the product could not completely retain its compact pellet form. In contrast, the condition of 280 °C and 90 bar provided the highest energy yield of 104.73%. These results indicate that torrefaction under mechanical pressure can improve the solid fuel properties of durian peel. The conditions in the range of 280–300 °C under 60–90 bar appear to be more suitable in terms of the balance among fuel quality, energy yield, and the ability of the product to retain its compact form.